2008
DOI: 10.1590/s1516-35982008001200013
|View full text |Cite
|
Sign up to set email alerts
|

Relação cálcio:fósforo disponível e níveis de fitase para poedeiras semipesadas no primeiro e segundo ciclos de postura

Abstract: RESUMO -Dois experimentos foram realizados para investigar a relação cálcio (Ca):fósforo disponível (Pd) e o nível de fitase (UF) no primeiro e segundo ciclos de postura. No primeiro ciclo de postura, 128 aves foram distribuídas em arranjo fatorial 3 × 2 + 1, composto de três relações Ca:Pd (14:1 = 4,2% Ca e 0,30% Pd; 12:1 = 3,5% Ca e 0,30% Pd; e 9:1 = 3,5% Ca e 0,38% Pd), dois níveis de fitase (0 e 600 UF) e uma relação Ca:Pd controle (11:1 -4,2% Ca e 0,38% Pd). No segundo ciclo de postura, 240 aves foram dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
1
0
3

Year Published

2010
2010
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 16 publications
1
1
0
3
Order By: Relevance
“…The results obtained in the present study on the effects of calcium levels on egg specific gravity are consistent with those of Silva et al (2008), who reported better egg specific gravity when increasing dietary calcium levels from 3.5 to 4.2%. However, Murata et al (2009) did not observe any effects of calcium levels (3.75 to 4.55%) on that parameter.…”
Section: Effects Of Dietary Clinoptilolite and Calcium Levels On The supporting
confidence: 92%
“…The results obtained in the present study on the effects of calcium levels on egg specific gravity are consistent with those of Silva et al (2008), who reported better egg specific gravity when increasing dietary calcium levels from 3.5 to 4.2%. However, Murata et al (2009) did not observe any effects of calcium levels (3.75 to 4.55%) on that parameter.…”
Section: Effects Of Dietary Clinoptilolite and Calcium Levels On The supporting
confidence: 92%
“…This can be explained by the greater quantity of phosphorus contained in this diet, which could have hampered the availability of calcium, and, in an attempt to circumvent this situation, the hens reduced production, but maintained the egg quality. In this sense, Silva et al (2008), working with different calcium:phosphorus ratios (9:1; 12:1 and 14:1) in diets for layers, observed that the increase in the ratio from 9:1 to 14:1 improved egg production linearly. These authors also verified effect from the calcium:phosphorus ratios on egg weight, egg mass and feed conversion per egg mass, and concluded that the calcium:phosphorus ratio of 14:1 (calcium at 42 g/kg and phosphorus at 3 g/kg) would ensure satisfactory performance of brown egg layers in the period from 28 to 44 weeks of age.…”
Section: Resultsmentioning
confidence: 99%
“…Segundo Faria et al (2000), ao estudarem a influência da idades de poedeiras Hy Line -W36 sobre o desempenho e qualidade interna e externa dos ovos, observaram que aves mais velhas apresentam valores inferiores de produção e conversão alimentar, porém com maior peso dos ovos quando comparados com aves mais jovens. De acordo com Lesson & Summers (2001); Silva et al (2008), as recomendações dos níveis de fósforo disponível (Pd) para poedeiras leves no período de postura, variam 0,15 até 0,50%.…”
Section: Pubvetunclassified
“…As recomendações dos níveis de Pd para poedeiras leves apresentam variações em relação ao longo do seu período produtivo, pois tanto nas pesquisas pubilcadas quanto nos manuais das linhagens, as estimativas variam de 0,15 até 0,50% Leeson & Summers (2001); Silva et al, (2008).…”
Section: Pubvetunclassified
See 1 more Smart Citation